ALGORITHMIC SOFTWARE OF DIAGNOSE AND SERVICEABILITY OF ATTITUDE AND STABILIZATION SATELLITE SYSTEM RESTORATION MODULES - Kulik, A. S.; Luchenko, O. A.; Firsov, S. N. (Radio Electronics, Computer Science, Control, 2012)
Unified description of the processes in the model blocks and the satellite system as a process of development of abnormal situations and process of it’s parry is presented. In addition, fourlevel scheme of parameterization of the direct criterion of failure is offered. Models and tools of satellite systems serviceability restoration are presented.